Psycho-social perspective of COVID-19 in Nepal - Maharjan, Sharmila (Applied Science and Technology Annals, 2020)
This ‘opinion article’ is based on World Health Organization (WHO) news and online publications along with the cases handled by the writer. It aims at overviewing psycho-social angle of collectivistic social structure of Nepal during the pandemic called COVID-19 caused by Coronavirus. Majority of Nepalese are dependent on agriculture, remaining on private or public services either in or out of the country. COVID-19 entered the world health threatening their existence, authority and leaving social system in halt. Coronavirus attacked breathing system and lungs claiming hundreds of thousand people’s lives around the world. No vaccine or medicine to combat it has been developed till date. Educational, professional and service organizations have been shut down leaving families isolated from friends and relatives. People are living with fear, denial, panic reactions, dissociation, depression, and socially distressed in ‘lockdown’ condition. It can damage trust in authority and socialization pattern as after-effect. Doctors, Politicians, educators, local government, social workers, psychologists and people themselves can reduce negative psycho-social effects occurring in future. Emotional management (situational awareness and acceptance), relationship management, meditation and relaxation exercises can contribute positively in reducing psychological problems of COVID-19.